Innovation in Micro, Small and Medium Sized Enterprises: New Product Development, Business Model Innovation and Effectuation - Jukka Heikkilä; Marikka Heikkilä (Slovenia, 2022)
Digitalization increases the need for innovation of the business models to a new high, also in micro, small and medium sized businesses (SMEs). Every third SME is engaged in Business Model Innovation (BMI) activities, but few of them in a systematic manner. Earlier empirical and theoretical research suggest that BMI is, and should be, an iterative process of adjustments in pursuit for better performance and success with New Product Development (NPD). NPD and BMI research streams use causal constructs with focus on external technology driven or market driven internal resource optimization. Studies on effectuation and bricolage, in turn, indicate that entrepreneurs’ passion, curiosity, and originality can compensate limited resources for innovation in SMEs. Building on these approaches, we propose a framework to analyze innovation in SMEs with case studies. The empirical data was collected in in Horizon2020 funded Envision project, where we use multiple case study approach. For this study, we select failed, surviving, and successful BMI cases to recommend effective BMI for SMEs and line out directions for future research. Keywords: • Business Model Innovation • New Product Development • Effectuation • Bricolage • SME • Market strategy • Performance
30th Bled eConference: Digital Transformation – From Connecting Things to Transforming Our Lives